Filling a theoretical void: The lived experiences of “coloured” women as mathematics educators in higher education - Kenny, S.; Davids, N. (South African Journal of Higher Education, 2022)
Thanks to intense prohibition and regulation of access to higher education during apartheid, a significant number of teachers from historically marginalised groups did not necessarily enter the profession as a first choice or as a desirable profession. Instead, post-schooling choices were based on access and financial support, restricting many marginalised groups to enrol at teacher training colleges. Beyond schools, there were no career pathways for “coloured”, “black”, and “Indian” teachers to teach at a higher education level. In mathematics education, the challenges experienced by “coloured” women are especially pronounced yet unexplored. To date, the dominant literature has leaned towards a negative portrayal, informed by stereotypical imagery and caricature. By exploring the lived experiences of six “coloured” women, who succeeded in establishing themselves as mathematics educators in higher education, the article is driven by a twofold imperative. On the one hand, it seeks to highlight the intersectional barriers of discrimination and marginalisation encountered by these women during apartheid and democratic South Africa. On the other hand, the article is interested in filling the theoretical void on the lives and capabilities of “coloured” women as mathematics educators in higher education.